Bentuk Penyajian Tari Galombang Sanggar Umbuik Mudo dalam Pesta Perkawinan di Nagari Sungai Asam, Kabupaten Padang Pariaman - Aprilia Putri Amanda; Nerosti Nerosti (SENDRATASIK UNP, 2023)
This study aims to describe and analyze the form of presentation of the Galombang Dance at Sanggar Umbuik Mudo at a wedding party and to reveal the form and sequence of the entire presentation of the Galombang Dance at a wedding party. This type of qualitative research uses a descriptive analytical method. While the main instrument is the researcher himself and requires tools in collecting data in the field, namely in the form of stationery and photo cameras. Data collection techniques in the form of literature, observation, interviews and documentation. The data analysis technique is by collecting data, describing the data and concluding the data. The results showed that the Galombang dance at the Umbuik Mudo Studio was a creative dance danced by 6 dancers, consisting of 1 male and 4 female dancers and 1 carano carrier. The movements of the male dancers consist of 6 movements, while the movements of the female dancers consist of 16 movements. The two-row floor pattern stretches backwards with two performances, that is, after the carano presenter offers betel nut to the guest of honour, the dancers continue the dance with a faster tempo. The costume for the female dancers is to wear a creations brackets shirt, salempang, songket skirt and the head wears a lenggek duo horn and uses accessories, namely lace, yellow net cloth, talepon earring, suntiang limo finger and kaban necklace and gold cakiak necklace. The accompanying music used in this performance is gandang, tambua, bass guitar, bansi, jimbe and talempong.